2021
DOI: 10.1108/oir-01-2021-0011
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the DeLone and McLean models in e-learning success: the moderating role of user type

Abstract: PurposeReviewing the existing literature in the field of e-learning success reveals a considerable number of studies that primarily investigate the causal relationships proposed by the DeLone and McLean (D&M) information system (IS) success model. However, the various relationships in the D&M model have found different levels of support or even contradictory results within the empirical literature. To synthesize the existing knowledge in the field of e-learning success, the authors have conducted a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 94 publications
(104 reference statements)
1
23
0
Order By: Relevance
“…Xu and Du (2022) observed a significant influence of SysQ on US regarding the digital library. Previous meta-analyses in an organizational context (Kaur and Chauhan, 2018) and e-learning success context (Pour et al, 2022) showed a significant relationship between SysQ and US. Pour et al (2022) also provided a positive relationship between SysQ and IU.…”
Section: System Qualitymentioning
confidence: 91%
See 2 more Smart Citations
“…Xu and Du (2022) observed a significant influence of SysQ on US regarding the digital library. Previous meta-analyses in an organizational context (Kaur and Chauhan, 2018) and e-learning success context (Pour et al, 2022) showed a significant relationship between SysQ and US. Pour et al (2022) also provided a positive relationship between SysQ and IU.…”
Section: System Qualitymentioning
confidence: 91%
“…Previous meta-analyses in an organizational context (Kaur and Chauhan, 2018) and e-learning success context (Pour et al, 2022) showed a significant relationship between SysQ and US. Pour et al (2022) also provided a positive relationship between SysQ and IU. Hence, based on evidence in the extant literature, the researchers hypothesized a significant positive relationship of SysQ with IU and US regarding libraries.…”
Section: System Qualitymentioning
confidence: 91%
See 1 more Smart Citation
“…This study extends Bagozzi’s self-regulation theory on the continuous usage intention of social networks. DeLone and McLean’s model is the well-established model to study the effect of system quality features (Shim and Jo, 2020; Çelik and Ayaz, 2021; Jami Pour et al , 2021), while TAM is used to study the adoption intention of the particular social network (Lin et al , 2014; Liu et al , 2019). The study explores the effect of system quality features (appraisal) on the perceived usefulness and attitude (emotional reaction) for the continuous usage (coping response) of social network applications.…”
Section: Hypotheses Development and Conceptual Frameworkmentioning
confidence: 99%
“…System quality has been found expressively influence users' satisfaction and perception of the overall success of using the system. Different studies over a while have demonstrated the importance of system quality in the adoption intention and the continuous usage intention of information systems (Wixom and Todd, 2005; Lin, 2008; Sharma and Sharma, 2019; Al-Fraihat et al , 2020; Jami Pour et al , 2021). Specifically, studies have found the effect of system quality features on the perception of usefulness and, thus, the continuous usage of different information systems (Ogbanufe and Gerhart, 2018; Al-Fraihat et al , 2020; Doshi, 2021; Ullah et al , 2021).…”
Section: Hypotheses Development and Conceptual Frameworkmentioning
confidence: 99%